Effective stress analysis of dynamically installed anchor installation in rate-dependent clay. (15th December 2022) - Chang, K.; Wang, D.; Hossain, M.S.; Kim, Y.H.; Qin, W.
Abstract: Accurate prediction of the final embedment depth and installation-induced excess pore pressure of dynamically installed anchors (DIAs) are prerequisites for the design of subsequent anchor set-up during a waiting period and capacity under operational loadings. This paper presents a dynamic large deformation finite element approach within the effective stress framework and investigates the installation behaviour of DIAs in clay. An elasto-viscoplastic model is adopted to capture strain rate dependency of the undrained shear strength. Development of excess pore pressure for various impact velocities, anchor geometries, viscosity parameters are quantified. An expression is proposed for estimating the final embedment depth of DIAs in clay. Highlights: A dynamic LDFE approach within the effective stress framework is developed, incorporating a strain rate-dependent model. The excess pore pressures caused by rapid penetration of a dynamically installed anchor can be captured. A simple equation is proposed to predict the final embedment depth of anchor.